Repeated Cases Of Deaths And Tragic Disasters The Causes And Integrated, Sustainable Solutions According To The Indonesian Lsipi Family - Darmawijaya bin Idris bin Idris; Hasnidar Hasnidar; Anni Atiqah Mahdiyyah; Anni Adilla Zakiyyah; Anni Adiva Rahmatillah; Anni Adinda Shofiyyah; Muhammad Fajar Islami Wijaya; Anni Anum Islamiyah Wijaya (International Journal of Health Engineering and Technology, 2026)
This study aims to explain “Repeated Cases of Deaths and Tragic Disasters: Their Causes and Integrated, Sustainable Solutions According to the LSIPI Family of Indonesia.” The method used in this study is the constructive critical historical method. The study finds that the main cause of repeated deaths and tragic disasters is the lack of integration between religious knowledge and academic knowledge in both theory and methodology. This phenomenon causes individuals, families, communities, organizations, companies, nations, and states throughout the world to experience helplessness (sterility) in preventing deaths and tragic disasters. This condition triggers economic losses, tragic deaths, destruction of business places, destruction of homes, and may even lead to Nuclear War, World War, and premature Doomsday. The only solution in the field of science and knowledge to overcome this helplessness (sterility) is to conduct in-depth research on religious knowledge and academic knowledge so that these two forms of knowledge may unite into one new, perfect, and blessed academic force. This success would become a very important and invaluable first step for every individual, family, community, organization, company, nation, and state in preventing economic losses, tragic deaths, destruction of business places, destruction of homes, Nuclear War, World War III, and premature Doomsday worldwide after COVID-19. This success is the key to preventing the negative impacts of religion and academic science, as explained by Albert Einstein, who said: “Religion without academic science is lame. Academic science without religion is blind.” This success would cause religious knowledge and academic knowledge to work in one complete unity through a new, perfect, and blessed academic science called Islamic Academic Science. This Islamic Academic Science is offered by the LSIPI Family of Indonesia as an integrated and sustainable solution in preventing and overcoming repeated deaths and tragic disasters in the end times. In the perspective of the Qur’an, this Islamic Academic Science is the knowledge commanded by Allah in Surah Al-‘Alaq verses 1–5 more than 1,400 years ago. This Islamic Academic Science is the result of our family’s independent experience and research in preventing chronic trauma and mental disability for 23 years (2002–2025), so that it would not end in heart attacks, strokes, schizophrenia, suicide, or premature death, while at the same time becoming a path for our family to achieve peaceful life, independence, and sustainable total recovery from chronic trauma, mental disability, and their complications. Facilitating multicultural societies (Muslims and non-Muslims) in achieving Sustainable Happiness, in accordance with the prayer taught by Allah in Surah Al-Baqarah verse 201, is the highest achievement that can be obtained through the teaching and development of Islamic Academic Science as the discovery and product of the LSIPI Family of Indonesia through 23 years of independent thought and research.